Kinematic and kinetic analysis of canine thoracic limb amputees at a trot - Jarvis, Sarah, author; Reiser, Raoul, advisor; Worley, Deanna, committee member; Haussler, Kevin, committee member (Colorado State University. Libraries, 2011)
Most dogs appear to adapt well to the removal of a thoracic limb, but clinically there is a particular subset of dogs that still have problems with gait that seem to be unrelated to age, weight, or breed. The purpose of this study was to objectively characterize biomechanical changes in gait associated with amputation of a thoracic limb. Sixteen amputees and 24 control dogs of various breeds with similar stature and mass greater than 14 kg were recruited and participated in the study. Dogs were trotted across three in-series force platforms as spatial kinematic and ground reaction force data were recorded during the stance phase. Ground reaction forces, impulses, and stance durations were computed as well as stance widths, stride lengths, limb and spinal joint angles. Kinetic results show that thoracic limb amputees have increased stance times and vertical impulses. The remaining thoracic limb and pelvic limb ipsilateral to the side of amputation compensate for the loss of braking, and the ipsilateral pelvic limb also compensates the most for the loss of propulsion. The carpus, and ipsilateral hip and stifle joints are more flexed during stance, and the T1, T13, and L7 joints experience significant differences in spinal motion in both the sagittal and horizontal planes throughout the gait cycle stance phases. The spine, carpus, and ipsilateral hip and stifle joints are of most concern when considering the biomechanical impact that a thoracic limb amputation may have for a given dog.
Keywords: canine; trot; limb amputation; kinetics; kinematics